Use of Intravenous Vitamin C in Critically Ill Patients With COVID-19 Infection. (February 2023) - Li, Matthew; Ching, Tsung Han; Hipple, Christopher; Lopez, Ricardo; Sahibzada, Asad; Rahman, Habibur
Introduction: The pathophysiology for Coronavirus Disease 2019 (COVID-19) infection is characterized by cytokine oxidative stress and endothelial dysfunction. Intravenous (IV) vitamin C has been utilized as adjuvant therapy in critically ill patients with sepsis for its protective effects against reactive oxygen species and immunomodulatory effects. The primary objective of this study was to evaluate the effects of IV vitamin C in critically ill patients with COVID-19 infection. Methods: Retrospective observational cohort study with propensity score matching of intensive care unit (ICU) patients who received 1.5 grams IV vitamin C every 6 hours for up to 4 days for COVID-19 infection. The primary study outcome was in-hospital mortality. Secondary outcomes included vasopressor requirements in norepinephrine equivalents, ICU length of stay, and change in Sequential Organ Failure Assessment (SOFA) score. Results: Eight patients received IV vitamin C and were matched to 24 patients. Patients in the IV vitamin C group had higher rates of hospital mortality [7 (88%) vs. 19 (79%), P = 0.049]. There was no difference in the daily vasopressor requirement in the treatment group or between the 2 groups. The mean SOFA scores post-treatment was higher in the IV vitamin C group (12.4 ± 2.8 vs. 8.1 ± 3.5, P < 0.005). There was no difference in ICU length of stay between the treatment and control groups. Conclusion: Adjunctive IV vitamin C for the management of COVID-19 infection in critically ill patients may not decrease the incidence of mortality, vasopressor requirements, SOFA scores, or ventilator settings.